O impacto das boas práticas de governança corporativa no desempenho de portfólios de empresas listadas na Bovespa - Elizangela Adriana de Castro Silva (2008)
The goal of this research is to evaluate if the participation of Brazilian stock companies in BOVESPA Different Levels of Corporate Governance (NDGC) contributes to acquire value earnings to the rational investors when they create an investment portfolio based on risk and return. Initially, it can be expected that companies that follow transparent rules,equality on stockholder treatment, rendering of accounts and corporate responsibility would tend to be recognized by investors, employees and creditors, what would rise its market value. However, empirical researches that try to relate good corporate governance practices withcompany performances show conflicting results. Because of this, it is not possible to conclude that there are such relations. This research intends to aggregate contributions to this theme, evaluating the engagement of listed companies in NDGC in investor perspective, trying measure if the capital representative papers selection of these companies makes possible the expansion of efficient frontiers and, therefore, represent a genuine gain in investor values. In this sense, the analysis was based on portfolio generation located in efficient frontiers built in accordance with Markowitz (1952) designations. In these portfolios, average differencestatistical tests were applied in portfolio returns conceived by Brazilian stock companies in BOVESPA Different Levels of Corporate Governance (NDGC) and in BOVESPA Traditional Market, separately, in 1999-2000 and 2005-2006 periods. To analyse if, in fact, corporate governance adds value to investors it was created a general table to make comparisons: a) two different periods: 1999-2000 and 2005-2006; b) two different company groups: one constituted by companies that didnt join to BOVESPA governance levels, the Traditional Corporative Governance Companies (ETGC); another constituted gathering the previousgroup plus companies with Brazilian stock companies in BOVESPA Different Levels Of Corporate Governance (ETGC+EMGC); c) three portfolio sizes: composed by 10, 20 or 30 assets; d) three different types of risk in order to consider different risk aversion investor profiles. The results showed in a strong way that it can have earnings if assets are selected from Brazilian stock companies in BOVESPA Different Levels Of Corporate Governance (NDGC). Then, after the NDGC implementation in 2001, significant differences were found in portfolio returns constituted by (ETGC+EMGC) companies compared with ETGC companies. In spite of the exploratory nature of this research witch imposes limits andrestraints to conclusions, the results show strong statistical evidences pointing to conclude that a greater corporate governance level really lead to greater earnings to rational investors who search for a maximization of returns related to investment portfolios.